2010
DOI: 10.1021/ie100259e
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infinite Dilution Activity Coefficients for Determining Binary Equation of State Parameters

Abstract: Infinite dilution activity coefficients can be determined relatively fast from several experimental techniques. Literature values for the infinite dilution activity coefficients are used to determine a binary interaction parameter of the perturbed-chain polar statistical associating fluid theory (PCP-SAFT) equation of state. The model is, subsequently, applied to the full concentration range of binary mixtures, and the results are compared to experimental data from literature. The applicability of the method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In literature, this technique has been used with many different polymeric materials, always with good results 16, 17. Another important point is that it has been demonstrated that the obtained values with this technique (at solvent infinite dilution conditions) can be extrapolated to the overall composition range 18…”
Section: Introductionmentioning
confidence: 95%
“…In literature, this technique has been used with many different polymeric materials, always with good results 16, 17. Another important point is that it has been demonstrated that the obtained values with this technique (at solvent infinite dilution conditions) can be extrapolated to the overall composition range 18…”
Section: Introductionmentioning
confidence: 95%
“…33 There has been considerable interest in predicting these coefficients 1821,30,3342 due to their use in phase equilibria studies in chemical engineering applications. 14,15,29,36…”
Section: Methodsmentioning
confidence: 99%
“…For example, limiting activity coefficients can be used to determine partition coefficients for a dilute species between two phases, which is critical in predicting the bio-accumulation of long-lived chemicals in the environment and food chain [2]. Furthermore, limiting activity coefficients of each component in a binary mixture can be used to parameterize binary interaction excess Gibbs free energy models to make phase equilibrium calculations over an entire range of concentrations [8,[11][12][13]. These parameterizations are particularly advantageous for maximizing the efficiency of separation processes, which comprise a large majority of chemical plant operations and costs.…”
Section: Introductionmentioning
confidence: 99%